An inflammation-targeted nanoparticle with bacteria forced release of polymyxin B for pneumonia therapy. Issue 41 (30th August 2022) - Zhang, Peisen; Ouyang, Qiuhong; Zhai, Tianshu; Sun, Jing; Wu, Jun; Qin, Feng; Zhang, Ni; Yue, Saisai; Yang, Xinchen; Zhang, Hanyi; Hou, Yi; Deng, Li; et al.
Abstract : PMB-HA nanoparticles constructed by self-assembly of hyaluronic acid and polymyxin B can precisely target the CD44 receptors over-expressed in pneumonia region and kill bacteria through the competitive binding of polymyxin B and lipopolysaccharide. Abstract : The epidemic of multidrug-resistant Gram-negative bacteria is an ever-growing global concern. Polymyxin B (PMB), a kind of "old fashioned" antibiotic, has been revived in clinical practice and mainly used as last-line antibiotics for otherwise untreatable serious infections because the incidence of the resistance to PMB is currently relatively low in comparison with other antibiotics in vivo owing to the unique bactericidal mechanism of PMB. However, serious adverse side effects, including nephrotoxicity and neurotoxicity, hamper its clinical application. Herein, we describe the development of a nanoparticle that can target sites of inflammation and forcedly release PMB specifically in the area of Gram-negative bacteria. This particle was constructed through the electrostatic self-assembly of hyaluronic acid (HA) and PMB molecules in order to realize the safe and effective treatment of pneumonia. After systemic administration, PMB-HA nanoparticles were found to actively accumulate in the lungs, precisely target the CD44 receptors over-expressed on the membrane of activated endothelial cells in inflammatory sites, and then come into contact with the bacteria resident in the damaged alveolar-capillary membrane. Due to the electrostatic and hydrophobic interactions between PMB and the lipopolysaccharide (LPS) in the outer membranes of bacteria, the PMB molecules in the PMB-HA nanoparticles are expected to escape from the nanoparticles to insert into the bacteria via competitive binding with LPS. Through shielding the cationic nature of PMB, PMB-HA nanoparticles also possess outstanding biosafety performance in comparison to free PMB. It is thus believed that this smart delivery system may pave a new way for the resurrection of PMB in the future clinical treatment of bacterial inflammatory diseases.